Réunir, conserver, faire connaître : le musée de l’hellénisme réfugié à Kavala, les Archives historiques de l’hellénisme réfugié à Kalamaria (Salonique) et le Foyer de Néa Smyrni - Maria Kazantzidou; Eleni Anastassiadou-Zacharopoulou; Manolis Zacharopoulos; Dimitra Vlachou (Cahiers Balkaniques)
Abstract: here we present three examples of the achievements of associations and municipalities to collect, preserve and make known the refugee Hellenism, the Museum of Refugee Hellenism in Kavala, the Historical Archive of Refugee Hellenism in Kalamaria (Thessaloniki) and the Foyer of Nea Smyrni (Athens)